PROACTIVE APPROACHES TO RUNNING COMPETENCIES AND FUNCTIONS BETWEEN SUPERVISION LOGIC AND EXPECTATION LOGIC UNDER HUMAN RESOURCE MANAGEMENT (Rafidain Bank model) - Nadeem, Oday Zuhair Mahmoud (International Journal of Psychosocial Rehabilitation, 2020)
–participative management seems to bring new hope and appears today not only as a vector for mobilizing the energies of the company, but also and above all as the key to a social and organizational peace once aborted and organize the work of men and women, the company seems undeniably attracted Indeed, the image of the absolute monarch and paternalist leader, having the monopoly of knowledge, language, authority and power, now seems unsuitable for news realities of the world of work, where the organization is no longer just an economic institution and technical, but a social arena where all the various actors must find this but between authoritarianism and exploitation on the one hand, servility, revolt and resignation on the other, the participation seems to have become over time, the realm of ambiguity, vagueness, others, participation has entered the era of suspicion, mistrust, skepticism and even of hostility, no doubt because of the long conflicting traditions which once marked the This article suggests that participation as a singular experience is a narrow path, conquest constantly renewed, difficult and full of pitfalls, which encounters many obstacles and which is obviously neither for the anxious nor for the skeptics. Indeed, the immaturity and the complexity of the organizational structures, the choices and the constraints imposed on managers and the cultural revolution that this form of management implies, leads us to believe that participation is a process that requires a framework significant time and which must not only be rooted on solid foundations, but also and above all take into account, whatever its forms, historical, economic realities.